Penerapan Alternatif Terhadap Penahanan (Alternatives To Detention) dalam Menangani Permasalahan Pengungsi Luar Negeri di Indonesia - Wicipto Setiadi; Mario Johanes Caesar Siagian (Faculty of Law, Universitas Padjadjaran, 2019)
In recent years, the numbers of refugees who transit in Indonesia are increasing. Since Indonesia is a state that upholds and respects human rights, the Indonesian government has an obligation to provide the best treatment and protection for refugees while they settle in the Indonesian territory. One of responsibilities of the state for these refugees is to implement programs that are alternatives to detention through the National Action Plan Beyond Detention 2014-2019. After the issuance of the Action Plan, the Indonesian government has collaborated with UNHCR and IOM to implement alternatives to detention in Indonesia. The alternatives are to provide care and the best protection for refugees living in the Indonesian territory. Refugees have to live in Indonesia temporarily because of various factors from the third countries. They have to stay for a while without a clear period until they are transferred to a third country of settlement. There are various problems in determining alternatives to detention in Indonesia. This paper aims to analyze and examine the policy of handling the problem of refugees in Indonesia since Indonesia has not ratified the Refugee Convention 1951.Penerapan Alternatif Terhadap Penahanan (Alternatives To Detention) dalam Menangani Permasalahan Pengungsi Luar Negeri di IndonesiaAbstrakDalam beberapa tahun terakhir, angka pengungsi yang singgah di Indonesia untuk sementara waktu mengalami peningkatan. Kebijakan pemerintah Indonesia yang menghormati dan menghargai HAM, membuat pemerintah berkewajiban memberikan perawatan dan perlindungan terbaik bagi para pengungsi yang tinggal di Indonesia. Salah satu program perlindungan yang digagas pemerintah adalah melakukan alternatif terhadap penahanan (alternative to detention) melalui Rencana Aksi Nasional Beyond Detention 2014-2019, bersama UNHCR dan IOM. Alternatif in bertujuan untuk menyediakan perawatan dan perlindungan terbaik terhadap pengungsi yang tinggal sementara tanpa harus melibatkan penahanan pengungsi di rumah detensi, sampai mereka dipindahkan ke negara ketiga. Terdapat beberapa masalah yang menghambat penentuan alternatif terhadap penahanan di Indonesia. Tulisan ini bertujuan untuk menganalisis dan memeriksa kebijakan Indonesia dalam mengatasi permasalahan pengungsi walaupun Indonesia tidak meratifikasi Konvensi Pengungsi 1951.DOI: https://doi.org/10.22304/pjih.v6n1.a7